Nup116p and Nup100p are interchangeable through a conserved motif which constitutes a docking site for the mRNA transport factor Gle2p - Bailer, Susanne M.; Siniossoglou, Symeon; Podtelejnikov, Alexandre; Hellwig, Andrea; Mann, Matthias; Hurt, Ed (The EMBO journal, 1998)
Nup116p and Nup100p are highly related yeast GLFG nucleoporins, but only Nup116p is stoichiometrically bound to Gle2p, a previously identified mRNA export factor. A short Gle2p‐binding sequence within Nup116p (GLEBS; residues 110‐166) is sufficient and necessary to anchor Gle2p at the nuclear pores, whereas the carboxy‐terminal domain of Nup116p mediates its own nuclear pore complex (NPC) association. The GLEBS is evolutionarily conserved and found in rat/Xenopus Nup98 and an uncharacterized Caenorhabditis elegans ORF, but is absent from Nup100p. When the GLEBS is deleted from Nup116p, Gle2p dissociates from the nuclear envelope and clusters of herniated nuclear pores form. When the GLEBS is inserted into Nup100p, Nup100p‐GLEBS complements both the thermosensitive and NPC‐herniated phenotype of nup116− cells, and Gle2p is retargeted concomitantly to the NPCs. Thus, the in vivo function of Gle2p is strictly coupled to the short GLEBS within Nup116p which links this putative mRNA transport factor to the nuclear pores.